Analysis of the Role of Digital Technology in Improving Banking Customer Personalization - Dadang Agus Suryanto (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the role of digital technology in enhancing personalized services for banking customers. The development of digital technology has allowed banks to access customer data more effectively, which is then used to deliver more personalized services. This research employs a quantitative method with a descriptive and causal approach. Data were collected through a survey involving 300 customers from various banks that have utilized digital banking services. The findings of this study indicate that the use of digital technologies, such as mobile banking applications and internet banking, positively influences the level of personalized services received by customers. Additionally, the study also found that although customer satisfaction with digital banking services is relatively high, concerns about data security remain a challenge that needs to be addressed. The study concludes that digital technology plays a crucial role in improving the more personalized and relevant banking experience; however, banks must continue to develop security systems to ensure customer trust.